Analisis Pengaruh Persepsi Kualitas dan Persepsi Nilai terhadap Loyalitas Konsumen Pengguna Sarana Lapangan Olahraga Futsal di Bandar Lampung - Ihsan, Raden Ahmad; -, Herlina (Jurnal Bisnis Darmajaya, 2015)
The purpose of this research is to determine the influence of quality perception and score perception toward consumersâ loyalty of futsal sport field users in Bandar Lampung. Â The problem comes from the futsal field are the number of limited field which is had by the field owner, comfort, facility and venue, futsal field rent price is different at each of different level. It is seen from the condition above therefore the consumersâ perception indicates that consumersâ perception of quality and score perception about Dome sport field that Dome field has many fields compare to other futsal fields. This research used descriptive research type. The population is futsal sport field use analysis result mutiple linear regression means that there is an influence between quality perception and score perception toward consumersâ loyalty of futsal field users in Bandar Lampung.Â Key Words : Quality Perception, Score Perception, Consumersâ Loyalty